ENT 530 Social Media Portfolio: Kueh By Mom / Nur Shahira Alam Shah - Alam Shah, Nur Shahira (2021)
Kueh By Mom is a trademark of the Traditional Malay cakes sales businesses. We began this business with the goals of allowing the company to remain competitive in the local market. Our key goals are to provide services to produce Traditional Malay cakes in good quality at reasonable prices. We've been working with one store for almost 10 years now which is a shop that was developed to sell different breakfast foods that also sell different Malay Traditional cakes often sold under this shop. But on 6 November 2020, Kueh's By Mom began marketing as a single Malay Traditional cake dealer. Based on our customers' knowledge and support, who know our goods in a breakfast shop they say that our business helps them get Malay Traditional cake making services for banquets and feasts. Furthermore, average of our loyal customers is also fond of the taste of our Malay Traditional cakes because our staff, who specialises in Malay cakes, traditionally produces these items. We have a good response from customers because our company has been commercialised and marketed via social media such as Facebook, so they can find all our business updates and continue to order or buy directly in our restaurant for breakfast. The promotion of our sales revenues through the Facebook page will indirectly increase, which we are only currently targeting clients in the Klang Selangor region, particularly during the COVID-19 pandemic.